TRILOGY OF INTELLIGENCE AND ITS RELATION TO REVELATION (ANALYSIS OF THE POTENTIAL OF IQ, EQ, SQ) - Mulyati, Sri (Archipelago Journal of Southeast Asia Islamic Studies, 2023)
This research discusses IQ (Intelligence Quotient), EQ (Emotional Quotient), and SQ (Spiritual Quotient), it sounds like a new term, but it is not. IQ, EQ and SQ, in fact, are just new concepts presented by cutting-edge psychologists, against the various potentials of intelligence possessed by humans. Man from his birth has had the potentials of intelligence given by God. These intelligences grow and develop along with the development of human experience. The focus of this study is how does IQ (intelligence quotient), EQ (emotional quotient), and SQ (spiritual quotient) function? and how the Qur'anic revelation views the intelligences in man?. The method used in this research is a type of literature research with a historical approach. The result of this study is According to the revelation of the Koran, human beings have various psychological potentials and these potentials determine human qualities. These potentials are ruh, aql, qalb, and nafs. By modern findings these potentials are then translated into IQ, EQ, and SQ. These potentials allow humans to become kamil people and or become ignorant people